Nano-galvanic coupling for enhanced Ag+ release in ZrCN-Ag films: antibacterial application - Velasco, Sebastian Calderon (2016)
The antibacterial properties of materials developed for medical devices with embedded silver nanoparticles are enhanced by controlling the release of silver ions. In this study, a simple experimental procedure for the augmentation of the silver ion release from ZrCN-Ag coatings is described. The silver nanoparticles are embedded in an amorphous carbon matrix within the ZrCN coatings, to create nano-galvanic couples between the silver and the carbon phases. The galvanic couple promotes the oxidation of silver, and consequently, increases the silver release. It is demonstrated that coatings with a lower silver content, but integrating amorphous carbon phases, can release similar or even a larger amount of Ag+ ions than those with higher Ag content having just ZrCN and Ag phases. The antibacterial tests demonstrate that coatings with silver nanoparticles encapsulated into amorphous phase reveal a larger bacterial zone of inhibition compared to samples with similar or lower silver content. However, it is shown that the antibacterial effect of the coatings not only depends on the ability for silver ion release, but also on the availability of silver nanoparticles on the surface.